Development of a Four-Way Pinch-Type Servo Valve for Pneumatic Actuator - Kotaro Tadano; Yasumasa Ishida; Hisami Takeishi (Applied Sciences, 2020)
Pneumatic servo valves are key components of pneumatic servo systems. Multi-degree-of-freedom systems, such as robot systems, utilize many servo valves to control their actuators. However, conventional servo valves always consume air due to leakage even when the pneumatic actuator is not moving. Hence, the consumption flow rate of the entire system corresponds to a heavy load on the air compressor. Reduction in the leakage of servo valves contributes to lower requirements for the air compressor and saves energy. In this study, we develop a four-way pinch- type pneumatic servo valve that controls flow rates by pinching air tubes to realize a leak-free servo valve. A cam to control the aperture of the flow channel is newly designed, and a control system is established. Measurement results indicate high linearity in static flow characteristics and high dynamic characteristics corresponding to 30 Hz. We experimentally confirm a good position tracking property in the position control of a pneumatic cylinder by using the developed valve. Finally, evaluation results of air consumption in a robotic control application indicate that the developed valve contributes to a significant reduction in air consumption compared to that of a conventional spool-type valve.